A forensic investigation of the Taihe arch bridge collapse. (1st December 2018) - Xu, Xiaobing; Wang, Jintao; Wei, Jinxiao; Taciroglu, Ertugrul; Dai, Fei; Peng, Weibing
Highlights: The collapse analysis of the Taihe Bridge provides a new avenue for structure collapse analysis. Geometric nonlinearities should be considered under improper dismantling of the superstructure over its primary arches. Improper dismantling of the superstructure over its primary arches will lead to a disproportionate collapse. Abstract: The collapse of the Taihe Bridge—located in the Jiangxi Province of China—on September 11, 2016 during what was intended to be a controlled demolition is forensically investigated here using police reports, analyses of site surveillance videos, and a debris survey. Two sets of numerical simulations were conducted to verify the collapse mechanism estimated from the forensic site investigation. First set of simulations involved geometrically linear static analyses carried out to determine the critical collapse state before the bridge fell. The second set involved dynamic analyses of the collapse process wherein geometric nonlinearities were considered. Results showed that improper dismantling of the superstructure over its primary arches caused the piers to come under large unbalanced forces and consequently to go through rigid body rotations. Multiple plastic hinges emerged at various locations of the primary arches, which set a disproportionate collapse mechanism into motion. This study reconstructed the dismantling and collapse process of the bridge with reasonable accuracy. The analyses and the results presented herein should serve as useful references for proper demolition of similar arch bridges.